Cast partial denture with attachment: a preventive prosthodontics: Gigi tiruan kerangka logam dengan kaitan: sebuah prostodontik preventif - Eri Hendra Jubhari; Ratna Hadrizaini Booy (Makassar Dental Journal PDGI Makassar, 2021)
Cast partial dentures is one of several treatment options that can be applied to rehabilitate partial edentulism with distal extension. Cast metal as a denture base exerts stimulation to the underlying tissue, thus prevents alveolar atrophy. However, one of the disadvantages of partial dentures with metal framework is the obviously visible retentive components attached to it, which could interfere with esthetics. This problem could be solved by using precision attachment that helps improving the esthetics, retention, stability and durability of the denture. There are two types of attachments, namely the intracoronal and extracoronal attachments. In this article, extracoronal attachments were used because they provide better esthetics.